2010
DOI: 10.1080/1331677x.2010.11517420
|View full text |Cite
|
Sign up to set email alerts
|

Framework for Performance Measurement in Hospitality Industry – Case Study Slovenia

Abstract: Hotel organizations in transition economies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 2 publications
1
22
0
Order By: Relevance
“…Brander-Brown & McDonnell (1995), Phillips (1999), Atkinson & Brander-Brown, (2001), Ittner et al (2003), Banker, Potter & Srinivasan (2005), Haktanir & Harris (2005) and Ramdeen, Santos & Chatfield (2007) concluded that both financial and non-financial performance improve the overall performance of organizations. Other studies including that of Evans (2005) in the United Kingdom, Huang et al (2007) and Chen et al (2011) in China, Bergin-Seers & Jago (2007) in Australia, Min et al (2008) and Kim & Lee (2009) in Korea, Pavlatos & Paggios (2009) in Greece, Ivankovic et al (2010) in Slovenia and Eldeeb (2011) in Egypt confirmed the successful application of BSC as a performance measurement system in hospitality organizations.…”
Section: Literature Reviewmentioning
confidence: 82%
See 1 more Smart Citation
“…Brander-Brown & McDonnell (1995), Phillips (1999), Atkinson & Brander-Brown, (2001), Ittner et al (2003), Banker, Potter & Srinivasan (2005), Haktanir & Harris (2005) and Ramdeen, Santos & Chatfield (2007) concluded that both financial and non-financial performance improve the overall performance of organizations. Other studies including that of Evans (2005) in the United Kingdom, Huang et al (2007) and Chen et al (2011) in China, Bergin-Seers & Jago (2007) in Australia, Min et al (2008) and Kim & Lee (2009) in Korea, Pavlatos & Paggios (2009) in Greece, Ivankovic et al (2010) in Slovenia and Eldeeb (2011) in Egypt confirmed the successful application of BSC as a performance measurement system in hospitality organizations.…”
Section: Literature Reviewmentioning
confidence: 82%
“…Financial and non-financial measures are not substitutes, but non-financial measures are used as supplements to financial measures (Govindarajan & Gupta, 1985). Several research findings (Denton & White, 2000;Harris & Mongiello, 2001;Atkinson & Brander-Brown, 2001;Evans, 2005;Bergin-Seers & Jago, 2007;Huang, Chu & Wang, 2007;Min, Min & Joo, 2008;Kim & Lee, 2009;Pavlatos & Paggios, 2009;Ivankovic, Jankovic & Persic, 2010;Wadongo et al, 2010;Chen, Hsua & Tzengb, 2011) in performance management advocate the relevance of both financial and non-financial measures for a balanced report of hotel performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is not surprising, because frontline employees are the face of a service firm, play a crucial role in service delivery, can return aggrieved customers to a state of satisfaction through service recovery, and influence customers' perceptions of brand image (Činjarević et al, 2010;Ivankovič et al, 2010;Karatepe and Sokmen, 2006;Rajh and Došen, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Under these circumstances, hotel managers are in need of frontline employees who can deliver quality services to customers and deal with customer problems e¤ectively (cf. Awang et al, 2010;Ivankoviè et al, 2010;Yavas et al, 2010). Work engagement (WE), which refers to "a positive, ful…lling, work-related state of mind that is characterized by vigor, dedication, and absorption" (Schaufeli et al, 2002, p. 74), leads to positive employee outcomes (Bakker and Demerouti, 2008).…”
Section: Introductionmentioning
confidence: 99%